Modelo para implementação de um catálogo de serviços de TI - Ferreira, Rodrigo Kellermann (Universidade do Vale do Rio dos Sinos, 2011)
This study proposes to conduct a mapping of IT services in a technology company, in order to give better visibility to internal customers about the services available and align services to business objective. For this, we performed a literature search on the topic and was also carried out a case study involving some areas of the company.
Keywords: Catálogo de serviços; Governança de ti; Alinhamento estratégico; Catalog of services; IT governance; Strategic alignment